A qualitative assessment of the influence of family dynamics on adolescents' sexual risk behaviour in a migration-affected community. Issue 1 (1st January 2020) - Anyanwu, Felix Chima; Akinsola, Henry Abayomi; Tugli, Augustine Kwame; Obisie-Nmehielle, Nkechi
ABSTRACT: Purpose: Adolescents may be known to take risks, but they may also conform to societal norms if they are given proper guidance, implying that there is a need for proper monitoring. This qualitative study explores the influence of family dynamics on adolescents sexual risk behaviour within a migration affected community.Method: Using thematic analysis, we processed data collected from 13 adolescents and 10 parents.Results: The themes generated from our data include the following, "Household poverty", "Family conflicts", "Lack of discipline", "Parent-child closeness", "Generational gap between adolescents and their parents" and "Lack of sex education". Our study found that financial constrain was a major problem in this community, the impact of this was worse felt among adolescents who lived by themselves. In addition, some parents were delinquent, distant or detached from their adolescents. We also found evidence to suggest that couple conflict was a common occurrence, and this had negative influence on adolescent well-being and there sexual behaviour.Conclusion: In view of the deepening crisis of early sexual engagement among adolescents and the accompanying risk of unplanned pregnancy and sexually transmitted infections, it is imperative to foster adolescent friendly households where the parents/caregivers are empowered to support their adolescents.